Factors that Influence Financial Capability and Effectiveness: Exploring Financial Counsellors’ Perspectives - Victoria Vyvyan; Levon Blue; Mark Brimble (Australasian Accounting, Business and Finance Journal, 2014)
The financial capability of the community has become a topical issue in recent years around the globe. The role financial education plays improving financial capability is recognised by the G20 countries. With a plethora of programs, workshops, seminars and other resources available in the community, we find that there is little research that measures the impact/usefulness of these programs including what should be included in such programs. This study seeks to contribute to the understanding of the underlying determinants of financial capability by exploring the factors that influence this. Focus groups were conducted with financial counsellors in Queensland, Australia to explore factors that inhibit and promote financial capability. This included factors that impede the development of capability and the others that impact on the development of intention to engage in financially effective behaviour. We report that financial counsellors view confidence, self-esteem and self-belief as equally important determinants of financial capability. Also, gender and family socio economic status influence an individual’s ability to engage in financially effective behaviour. The results also found that adopting a short-term focus, rather than future orientation, is a key inhibitor of financial effectiveness. Consequently it is suggested that those developing financial capability programs address these behavioural and contextual factors rather than concentrating purely on literacy.
Keywords: financial capability; financial effectiveness; financial decision-making; financial behaviour